Structural properties and digestion of green banana flour as a functional ingredient in pasta. Issue 2 (3rd December 2015) - Zheng, Zeqi; Stanley, Roger; Gidley, Michael J.; Dhital, Sushil
Abstract : Gluten free pasta was made from raw banana flour in combination with vegetable gums and egg protein for comparison to pasta similarly made from wheat flour. Abstract : Gluten free pasta was made from raw banana flour in combination with vegetable gums and protein for comparison to pasta similarly made from wheat flour. After cooking, it was found that the banana flour pasta was less susceptible to alpha-amylase digestion compared to conventional wheat flour pasta. Release of glucose by alpha-amylase digestion followed first order kinetics with an initial rapid rate of digestion and a subsequent second slower phase. The structure of green banana pasta starch at the inner and outer pasta surfaces was observed under confocal laser scanning microscopy (CLSM) and the viscosities of the flour mixtures were measured by a Rapid Visco Analyser (RVA). The digestibility of banana flour pasta was found to be related, not only to the properties of the starch granules, but also to the protein network of the surrounding food matrix. The effects of gums and proteins on pasta formation and digestibility are discussed in the context of its potential use as a gluten free lower glycaemic alternative to conventional wheat based pastas.